Cutaneous Larva Migrans -A Case Report (TAJ: Journal of Teachers Association, 2009)
A case of cutaneous larva migrans came to the dermatology outdoor of Rajshahi Medical College Hospital with the complaints of migratory cutaneous itching lesion on her right hand. At the onset she had papules with mild itching on ventral aspect of her right hand. The papular eruption turned into a raised linear line progressed with tortuous course and finally ended at the medial aspect of right thenar eminence about one inch below the wrist crease. The lesion looked like a thin, raised serpiginous line with mild erythema. Complete blood picture shows high eosinophilic count, with mild anaemia and histopathology shows features of chronic dermatitis. But no larva was present in the lesion. Stool for routine examination shows eggs of Ancylostoma duodenale. The patient was diagnosed as cutaneous larva migrans . The patient was prescribed tab. Albendazole DS 400 mg. twice daily for 3 days and tab. Cetrizine 10mg. once daily for 10 days. The dose of Albendazole was repeated after 14 days.   doi: 10.3329/taj.v18i1.3305 TAJ 2005; 18(1): 49-50